Soil Organic Carbon Storage in Khlong Saeng Local Durian and Rubber Agroecosystem in Ban Ta Khun District, Surat Thani Province - Hwante, Phongsakon; Ruairuen, Watcharee (PKRU SciTech Journal, 2023)
The understanding of soil organic carbon (SOC) storage in agroecosystems are limited in southern Thailand. This study was performed to investigate the amount of SOC storage in the agroecosystem of local durian (Durio zibethinus) and rubber tree (Hevea brasiliensis) plantation in Ban Ta Khun District, Surat Thani Province. Soil samples were collected by non-disruptive and destructive methods at a depth of 0-30 cm from 3 stations of each agroecosystem in July and September 2022. Physical and chemical soil properties including soil bulk density, texture, pH, and SOC were analyzed. The results revealed that most of the soil texture in the local durian plot was sandy clay loam. The average soil bulk density ranged from 0.97-1.10 g/cm3, soil pH was moderately acid to very strongly acid (pH 4.62- 5.96), the SOC storage and soil organic matter (SOM) were 23.40-72.66 g C/m2 and 1.11-3.31%, respectively. On the other hand, in the rubber plot, the soil texture was silty clay with soil pH that was strongly acid to very strongly acid (4.60-5.39). The bulk density of the soil was in the range of 1.24-1.34 g/cm3. The SOC storage and SOM were 17.21-46.90 gC/ m2 and 0.84-2.10%, respectively. The SOC concentrations were positively correlated with soil moisture (P<0.01; R=0.45), pH (P<0.01; R=0.49), and sand particles (P<0.05; R=0.68), but a negative correlation with silt (P<0.05; R=-0.68) and clay (P<0.01; R=-0.82). However, there was no correlation between the SOC concentration and bulk density nor between SOC and soil electrical conductivity.